The coronavirus conundrum – A third wave? - Vaccines and viral variants - The pregnant woman and her child - Pacheco-Romero, José (2021)
The SARS-CoV-2 virus continues to reproduce rapidly and is showing more infectiousvariants. The second wave of the pandemic is subsiding in Europe and the UnitedStates of North America, but not in South America. In Peru, the number of deathshas more than doubled, with a higher mortality rate in men and in those over 70years of age. It has been corroborated worldwide that pregnant women suffer amore severe disease -sometimes with a process similar to preeclampsia- with agreater possibility of death than non-pregnant women and greater fetal death andprematurity. Initial vaccines developed in the USA and Europe are proving effective inreducing infections, hospitalizations and deaths in countries where vaccination hasadvanced more rapidly. It is being administered in pregnant women without majorside effects, and they are recommended to be vaccinated to avoid severe infection.As of now, the duration of immunity given by COVID-19 infection and by the vaccineis not known. A third booster dose and rebranding of vaccinees is being considered.And a third wave of infections is expected due to the emergence of the Brazilian andIndian (Delta) variants.